Masking noise reduces the anti-predator-like response to an acoustic stimulus: Application of Signal Detection Theory to fish behaviour - Helen A. L. Currie; Paul R. White; Timothy G. Leighton; Paul S. Kemp (PLoS ONE, 2025)
In studies of animal cognition, the influence of background masking noise on responses to any particular stimulus are often overlooked. In fish, there is little understanding of their response to targeted acoustic stimuli in the presence of high intensity (Sound Pressure Levels) environmental masking noise commonly experienced in the wild. In a controlled laboratory study, Signal Detection Theory was used to investigate coarse (startles) and fine-scale (swimming speed, group cohesion and alignment) responses of common carp (Cyprinus carpio) to pulsed tonal signals (170 Hz) differing in their signal-to-noise ratio (low, intermediate, or high) above either background ambient, or masking noise (fixed intensity Gaussian white noise: 120–3000 Hz). In comparison to independent control groups, fish exhibited a startle response, reduced their average swimming speed, increased group cohesion, and became more aligned at the onset of tonal stimuli under ambient noise. Signal discriminability was reduced under the masking noise conditions, with coarse-scale behavioural responses largely absent, and fine-scale responses suppressed but positively related to signal-to-noise ratio. This study enhances understanding of the potential ecological consequences of anthropogenically generated noise on the behaviour of fish and may help in the development of more effective environmental impact mitigation technologies, such as behavioural guidance systems, that use sound to induce avoidance.